Pendidikan Literasi Keuangan untuk Meningkatkan Minat Berwirausaha di Perguruan Tinggi Islam: Peran Efikasi Diri Sebagai Faktor Mediasi - Aqilla Pradanimas; Slamet Slamet (Universitas Islam Tribakti Lirboyo Kediri, 2023)
The high level of unemployment in Indonesia among undergraduates is a problem in itself for the Indonesian people. This happens because graduates prefer to look for instant jobs at institutions that already exist rather than opening their own job opportunities. One of the reasons is their lack of literacy regarding financial literacy and interest in entrepreneurship. This research aims to determine the relationship between students' financial literacy level and interest in entrepreneurship which is mediated by self-efficacy. The research was carried out using a quantitative approach to UIN Malang students. Data was collected by random sampling using Google Form via social media such as WhatsApp and Email. Data were analyzed using SmartPLS 3.29. The research results show that financial literacy has a positive and significant effect on students' entrepreneurial interest. Financial literacy has a positive effect on increasing self-efficacy and self-efficacy mediates the relationship between financial literacy and interest in entrepreneurship.